Nórmese en la ley orgánica de transporte terrestre, tránsito y seguridad vial, la formación de los conductores en base a los derechos humanos y constitucionales - Cambizaca Vera, Carlos Guillermo (2014)
The Ecuadorian State is subscriber of the Universal Declaration of Human Rights, which recognizes as fundamental rights of the people, life, personal integrity and health, legal rights are properly established as human rights in the Constitution of the Republic of Ecuador. Human rights mentioned in the previous paragraph, are constantly violated as a result of traffic accidents, which have a high incidence in Ecuadorian society, and that its causes among other things is the lack of a culture of respect from the conductors and drivers of motor vehicles, to the human rights of other persons involved in land transport, traffic and road safety. In reviewing the Land Transport Act, Traffic and Road Safety, and General Enforcement Regulations, you can determine that there is no legislation that is geared specifically to establish a requirement for obtaining title or driver's license, which applicants to obtain this document, proof of having received formal education about human rights of the people. Given the legal issues, it was decided that it is necessary to study and address it on extensive research, this being the purpose of this thesis entitled: "REGULATE IT IN LAW ON LAND TRANSPORT, TRAFFIC AND ROAD SAFETY, TRAINING DRIVERS BASED ON HUMAN RIGHTS AND CONSTITUTIONAL ". This report was developed in accordance with the rules laid down in the Regulations of the Academic Board National University of Loja, and methodological guidelines and formal are provided in the Legal Research Guide Race Mode law Distance Learning, and aims to ensure that there Ecuadorian society by the conductor and drivers of motor vehicles, due respect for human rights of the people, in order to guarantee legal certainty for all people in the field of individual and social endeavor.